One Health gains momentum in Africa but room exists for improvement - Fasina, F.O.; Bett, Bernard K.; Dione, Michel M.; Mutua, Florence K.; Roesel, Kristina; Thomas, Lian F.; Kwoba, E.; Ayebazibwe, C.; Mtika, N.; Gebeyehu, D.T.; Mtui-Malamsha, N.; Sambo, M.; et al. (Elsevier, 2022)
Objectives The degree of One-Healthiness of a system relates to the effectiveness of an institution to operate within the six main dimensions which identify to what extent it complies with One Health concept. This paper evaluates institutional compliance with One Health concept in 14 institutions from eight African countries.